2020
DOI: 10.20473/jkl.v12i1.2020.21-29
|View full text |Cite
|
Sign up to set email alerts
|

The Case of Leprosy in Work Area of Talango Health Center in Sumenep Regency: Case Control Study

Abstract: Introduction: Leprosy was caused by Mycobacterium leprae infection which attacks the peripheral nerves and human skin. A total of 39 cases of leprosy occurred in 2018 at the Talango Health Center and became the highest prevalence in Sumenep Regency each year. Multibacillary leprosy dominates in 76.92% of cases. This study aims to analyze the influence of physical environment factors of the home namely temperature, humidity, ventilation, occupancy density, natural lighting, wall types, and floor types on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…The physical environment of a house including ventilation and lighting needs attention; a physical environment that is not in line with minimum health standards will increase the risk of transmitting this disease. 32 In this study, it was concluded that there was no significant relationship between genders, occupations and medication adherence. These results are in line with other researchers, genders are not a determinant of adherence, although the incidence of leprosy is higher in men than women.…”
Section: Discussionmentioning
confidence: 69%
“…The physical environment of a house including ventilation and lighting needs attention; a physical environment that is not in line with minimum health standards will increase the risk of transmitting this disease. 32 In this study, it was concluded that there was no significant relationship between genders, occupations and medication adherence. These results are in line with other researchers, genders are not a determinant of adherence, although the incidence of leprosy is higher in men than women.…”
Section: Discussionmentioning
confidence: 69%
“…Selain itu sebagian besar rumah responden yang diteliti memiliki ventilasi hanya pada ruang tamu dan juga sebagian reponden memakai jendela yang permanen sehingga sirkulasi udara menjadi terhambat dan udara segar tidak dapat masuk kedalam ruangan. Selain itu, penelitian yang dilakukan oleh Rhomdani et al, (2020) menunjukkan bahwa luas ventilasi berhubungan dengan kejadian kusta di wilayah kerja Puskesmas Talango Kabupaten Sumenep. Dalam hasil penelitiannya menyatakan bahwa responden kasus memiliki ruang tidur yang tidak memenuhi persyaratan luas ventilasi yaitu <10% dari luas lantai.…”
Section: Metode Penelitianunclassified
“…Penelitian yang dilakukan oleh Idayani et al, (2017) bahwa kurangnya cahaya yang masuk ke dalam rumah dapat menyebabkan ruangan menjadi lembab sehingga bakteri mycobacterium leprae dapat tumbuh subur. Penelitian juga dilakukan oleh Rhomdani et al, (2020) Hasil penelitian menunjukkan bahwa rumah responden dengan kepadatan hunian yang tidak memenuhi syarat berjumlah 19 rumah (100%) pada kelompok kasus, sedangkan 5 rumah (26,3%) pada kelompok kontrol. Rumah responden dengan kepadatan hunian yang memenuhi syarat berjumlah 0 rumah (0%) pada kasus, sedangkan pada kelompok kontrol berjumlah 14 rumah (73,7%).…”
Section: Metode Penelitianunclassified